DETERMINAN FAKTOR YANG BERHUBUNGAN DENGAN MINAT PRIA PUS TIDAK MENGGUNAKAN KB MOP DI WILAYAH KERJA PUSKESMAS PURWOJATI - Pantiawati, Ika; Khosidah, Amik; Astuti, Iin (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
ABSTRACT: DETERMINANTS FACTORS RELATED TO THE INTERESTS OF MEN AGE FERTILE COUPLE FAMILY PLAN MOP NOT USE IN PUBLIC HEALTH CENTER OF PURWOJATI. MOP was a minor operative contraception method for a man which save, simple and effective,  need a short time for operation and do not need a general anesthesia. The factors that influenced low participate of man for doing the KB among limited socialization and promotion of man KB, high price to pay for MOP, lowing knowledge of man about KB, wife does not support them for KB, politic condition, social and community culture, and government commitment that has still not been optimal for supporting man KB. To found out the factors related to enthusiasm of man PUS does not use MOP contraception in the work area of Purwojati Public Health Center year 2014. The type of this research was analytical survey with cross sectional approach, The sample used purposive sampling technique with the number of samples amount 99 acceptors. The analysis used correlation Kendall Tau test. The result from correlation Kendall Tau test obtained P-value amount 0,000 indicated there was a relationship between knowledge with enthusiasm of man PUS does not use MOP contraception, p-value amount 0,000 indicated there was a relationship between motivation with enthusiasm of man PUS does not use MOP contraception, p-value amount 0,003 indicated there was a relationship between wife’s support with enthusiasm of man PUS does not use MOP contraception, and p-value amount 0,024 indicated there was a relationship between culture social with enthusiasm of man PUS does not use MOP contraception in the work area of Purwojati Public Health Center year 2014. There was a relationship between knowledge, motivation, and wife’s support with enthusiasm of man PUS does not use MOP contraception in the work area of Purwojati Public Health Center year 2014.  Keyword: Knowledge, Motivation, Wife’s  Support